Dysregulated sexuality and childhood trauma in eating disorders: Psychopathological, biological, and behavioural correlates. (13th April 2021) - D'Anna, G.; Castellini, G.; Rossi, E.; Cassioli, E.; Appignanesi, C.; Monteleone, A.M.; Rellini, A.H.; Ricca, V.
Abstract : Introduction: Sexual dysfunction is common in eating disorders (EDs), but its relevance is often overlooked. Objectives: To describe different ED clinical subgroups in terms of psychopathology, putative biological correlates, and consequences of dysregulated sexuality, focusing on the role of childhood trauma. Methods: Healthy controls (n=60), binge-purging (n=38), and restricting patients (n=24) were compared (age- and BMI-adjusted ANOVA; Bonferroni post-hoc tests), using total scores of Eating Disorder Examination Questionnaire (EDE-Q), Emotional Eating Scale (EES), SCL-90-R Global Severity Index (GSI), Barratt Impulsiveness Scale (BIS-11), Difficulties in Emotion Regulation Scale (DERS), Childhood Trauma Questionnaire (CTQ), Female Sexual Functioning Index (FSFI), Hypersexual Behaviour Inventory (HBI), and patients' hormonal profiles (gonadal and pituitary hormones, ghrelin). Self-reported voluntary termination of pregnancy (VTP) and promiscuous sexual activity were recorded. For ED patients (N=62), regression analyses between significant variables and HBI were carried, applying moderation models for different CTQ scores. Results: Table 1 outlines significant between-group comparisons (°: different from controls; *: different from restricting patients; p<0.05). Binge-purging patients had higher FSH, LH, and ghrelin levels, more VTPs and promiscuity. HBI showed significant correlations with EES, SCL-90-R-GSI, DERS, CTQ, and ghrelin levels. CTQ moderated interactions for DERS and EES (Figure 1). Binge-purging Restricting Controls F EDE-Q 3.86±1.20° 3.41±1.64° 0.85±0.83 67.32 EES 40.85±22.74°* 16.01±15.88 19.87±15.21 7.01 SCL-90-R GSI 1.73±0.65° 1.27±0.69° 0.68±0.44 20.32 BIS-11 62.47±9.91° 60.81±8.56 57.04±10.04 4.99 DERS 106.97±29.15°* 83.97±33.12 78.14±14.12 10.21 CTQ 55.32±21.06° 49.31±10.81° 38.02±8.32 15.24 FSFI 17.32±11.89°* 11.70±10.98° 29.32±7.45 24.02 HBI 28.75±13.89* 20.56±3.12 26.11±4.90 4.92 Conclusions: Dysregulated sexuality is linked to emotion dysregulation and childhood trauma. Binge-purging patients experience adverse behavioural consequences. Disclosure: No significant relationships.